2021
DOI: 10.3390/ijms22094743
|View full text |Cite
|
Sign up to set email alerts
|

Hemistepsin a Induces Apoptosis of Hepatocellular Carcinoma Cells by Downregulating STAT3

Abstract: Hemistepta lyrata (Bunge) Bunge is a biennial medicinal plant possessing beneficial effects including anti-inflammation, and hemistepsin A (HsA) isolated from H. lyrata has been known as a hepatoprotective sesquiterpene lactone. In this report, we explored the cytotoxic effects of H. lyrata on hepatocellular carcinoma (HCC) cells and investigated the associated bioactive compounds and their relevant mechanisms. From the viability results of HCC cells treated with various H. lyrata extracts, HsA was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Various studies have shown that autophagy is a potent mechanism for eliminating incorrect folded or aggregated proteins and maintaining the energy homeostasis to respond to stress [ 26 , 27 ]. Although the roles of crosstalk between apoptosis and autophagy have been studied [ 28 , 29 ], autophagy has been a widely used therapy for chemo-resistant cancer [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that autophagy is a potent mechanism for eliminating incorrect folded or aggregated proteins and maintaining the energy homeostasis to respond to stress [ 26 , 27 ]. Although the roles of crosstalk between apoptosis and autophagy have been studied [ 28 , 29 ], autophagy has been a widely used therapy for chemo-resistant cancer [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemistepsin A exhibited anti-HCC effect by disrupting MMP, up-regulating p53, p21, cleaved caspase-3 and cleaved PARP and reduced the expressions of cyclin D, CDK6 and Bcl-2. In HepG2 cells, Hemistepsin A-induced apoptosis was associated with its downregulation effect of STAT3 ( 58 ). The expression of cleaved PARP cells in Sub-G1 phase were increased, indicating that hemistepsin A induced apoptosis.…”
Section: Anti-hcc Mechanism Of Active Sesquiterpenoidsmentioning
confidence: 99%
“…Levels of reduced glutathione (GSH) and oxidized glutathione (GSSG) were determined by GSH/GSSG-Glo TM Assay (Promega, Madison, WI, USA), as described previously [33].…”
Section: Measurement Of Glutathionementioning
confidence: 99%
“…Protein extraction using radioimmunoprecipitation buffer, sodium dodecyl sulfatepolyacrylamide gel electrophoresis, electrotransfer of proteins onto a nitrocellulose membrane, incubation of the membrane with appropriate antibodies, and chemiluminescence detection were conducted as described previously [33]. For surface sensing of translation (SUnSET) assay, HepG2 cells under CST/Met (−) were incubated with 1 µg/mL puromycin for 30 min, and puromycin-integrated polypeptides were detected using an anti-puromycin antibody.…”
Section: Immunoblot Analysismentioning
confidence: 99%